GARITA Media: Students' Mathematical Communication in Solving Contextual Problems - Rosyadi, Alfiani Athma Putri; Cholily, Yus Mochamad; Suciati, Nur; Usmiyatun, Usmiyatun (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
Based on observation results, the mathematical communication skills of 6th-grade elementary school students are still relatively low. This can be seen during classroom learning activities or when taking exams, when they are faced with contextual story problems they have difficulty understanding and solving them. The implementation of this research activity aims to see effect GARITA media and the mathematical communication skills of 6th-grade elementary school students, as shown through the results of contextual problem assignment scores. Apart from looking at the connection between GARITA media and mathematical abilities, this research was conducted to increase students' understanding in solving contextual problems. GARITA media is a media in the form of story images which have the role of helping to illustrate the problems in story problems, making it easier for students to understand the content of contextual problems and solve them. This research uses quantitative methods with quasi-experiments. The population of this study were students at SD Muhammadiyah 3 IKROM Wage Sidoarjo. This research activity took data from 29 Zahrawi 6th grade students as the control group and 30 Haitam 6th grade students as the experimental group. The result of this research data was obtained by carrying out a post-test in the form of a contextual question test and a student response questionnaire. The data analysis techniques used in this research are normality test, homogeneity test, and hypothesis test. This shows a significant difference in the mathematical communication skills of students who received treatment using GARITA assistance with students who did not receive treatment. The homogeneity test result shows that homogeneity data based on post-test data shows a figure < 0,05. Hypothesis testing shows a significant influence based on the result of the independent sample t-test < 0,05. So, the result of this research indicates that GARITA media can influence the improvement of students' mathematical communication skills in solving contextual problems.